Effect Price Perception, Customer Relationship Marketing, and Trust on Serabi Notosuman Sales Mediated Customer Loyalty - Putri Alfiatur Rochimah; Muzakar Isa (ProBisnis : Jurnal Manajemen, 2023)
This study aims to analyze the effect of price perception, customer relationship marketing, and trust in sales on Serabi Notosuman with customer loyalty as a mediating variable. In this study, the population used was all buyers of Serabi Notosuman with a sample of 200 respondents. Sampling in this study used non-probability sampling with a purposive sampling technique. Data collection in this study was carried out by distributing questionnaires online. The data analysis used is Smart PLS version 3.2.9. The data testing method used in this study includes the outer model, which consists of covergent validity, discriminant validity, composite reliability, Cronbach's alpha and multicollinearity tests. Then the inner model consists of coefficient determination, goodness of fit, effect size test (f²), and hypothesis testing. The results in this study indicate that price perceptions have no significant effect on sales, price perceptions have a positive effect on loyalty, customer relationship marketing has a positive effect on sales, customer relationship marketing has no significant effect on loyalty, trust has a positive effect on sales, trust has a positive effect on loyalty, and loyalty has a positive effect on sales.